Ottoman Heritage in Bosnia and Herzegovina According to the Ottoman Archive Documents of the Government Presidency - Küçük, Mustafa (Prilozi za orijentalnu filologiju, 2017)
In almost all funds of Başbakanlik Osmanlı Arşivi (the Ottoman Archive of the Government Presidency), which is recognised by the world scientific workers as one of the richest in numbers and types of documents, being the first order source for the works of historians and researchers, there are thousands of documents related to Bosnia and Herzegovina. Since the Turks as of the first periods of their history had the initiative to write down their official procedures and, maintaining the collected state documents, set up the archive (Hazine-i Evrak), millions of documents were created relating to almost all spheres of tens of countries, which, under six and a half centuries long rule of the Ottoman Empire, covered the area of several million square kilometres. After the Ottoman Empire had disappeared from history, this rich archive material was taken over by the Republic of Turkey. This rich historic heritage, which is very important not only because it transfers from the past into the future historical-economic-military-politicalgeographic and religious information, but also because it simultaneously reflects the state.s official procedures and its bureaucratic materials from the periods it refers to, has an unachievable value in regard to the artistic merits as each individual sample, from the script and gilt in the documents to the paper and ink used, to the covers and jackets of the collections. It is natural that in this respect Hazine-i Evrak is the basic source for historical heritage of a region such as Bosnia and Herzegovina, to which the Ottoman Empire had always given advantage and tried to afford it the best of what it had itself. The Ottoman Empire, either in respect of the administration or in respect of the institutions realised in those provinces, always kept Bosnia and Herzegovina privileged in focus of its attention. Finally, back in 1478, Sultan Mehmed Fatih in the Imperial Ahdnama, which he issued to Bosnian priests (see Appendix 13), noted his benevolence towards Bosnian priests and their placing under his protection. Just as every procedure, every piece of information and every document created under the act where the Turks set up waqfs (endowments), was confirmed on the basis of the documents found today in the Başbakanlik Osmanlı Arşivi, as well as their seriousness when endowing property to Almighty God, so evident are these data in the Turkish-Islamic waqfs within and beyond the borders of the Republic of Turkey. At founding the waqfs, the Turks indeed took account that they by no means and under no circumstances should be damaged, and it is thanks to these religious-charitable-humanitarian institutions that they kept the social structure of the regions under their rule; justice, mercy and mutual assistance upright. They set an example of an incredibly high level of civilisation. The still existing waqfs are living witnesses to these. Both examples and summaries of the documents quoted in the paper clearly express this fact